Therapeutic Efficacy of Alpha-RIT Using a 213Bi-Anti-hCD138 Antibody in a Mouse Model of Ovarian Peritoneal Carcinomatosis - Derrien, Aurélie; Gouard, Sébastien; Maurel, Catherine; Gaugler, Marie-Hélène; Bruchertseifer, Frank; Morgenstern, Alfred; Faivre-Chauvet, Alain; Classe, Jean-Marc; Chérel, Michel (Frontiers in Medicine, 2015)
Purpose: Ovarian peritoneal carcinomatosis is a pathology for which effective cures are currently lacking. New research protocols seek to eradicate residual micrometastases following cytoreductive surgery by using Hyperthermic Intraperitoneal Chemotherapy (HIPEC), or Radioimmunotherapy (RIT). This study aims to firstly develop alpha-RIT using an anti-CD138 mAb radiolabeled with an alpha-emitter, bismuth 213 (213Bi-B-B4) and HIPEC in a nude mouse model, and secondly to compare and combine these techniques. Material and Methods: A murine model of postoperative ovarian peritoneal carcinomatosis was established. A pilot group of six mice received an intraperitoneal injection of luciferase-tagged SHIN-3 cells and bioluminescence was measured every day. Cytoreductive surgery was performed at day 14 (n=4) and 29 (n=2). Because the residual bioluminescence signal measured after surgery was equivalent to that obtained 3 days after the graft, HIPEC or alpha-RIT treatments were applied 3 days after the graft. Ten mice were treated by HIPEC with cisplatine (37.5 mg/mL), 11 with 7.4 MBq of 213Bi-B-B4, 7 with 11.1 MBq of 213Bi-B-B4 and 10 mice were treated with the combined therapy (HIPEC + 7.4 MBq of 213Bi-B-B4). Eleven mice received no treatment. Bioluminescence imaging and survival were assessed. Results: Alpha-RIT 7.4 MBq and 11.1 MBq significantly improved survival (p=0.0303 and p=0.0070 respectively) whereas HIPEC and HIPEC + alpha-RIT treatments did not significantly ameliorate survival as compared to the control group. Conclusions: Survival was significantly increased by alpha-RIT treatment in mice with peritoneal carcinomatosis of ovarian origin, however HIPEC alone or in combination with alpha-RIT had no significant effect.